2022
DOI: 10.3389/fmicb.2021.775665
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Endophytic Bacterial Diversity From Different Dendrobium Stems and Discovery of an Endophyte Produced Dendrobine-Type Sesquiterpenoid Alkaloids

Abstract: As the unique component of Dendrobium, dendrobine-type sesquiterpenoid alkaloids (DSAs) possess a variety of medicinal properties. It has been well documented that plant endophytes can in vitro synthesize secondary metabolites identical or similar to metabolites produced by their host plants. This study aimed to investigate the composition and distribution of endophytic bacteria of Dendrobium stems by Illumina MiSeq platform sequencing and cultivation-dependent methods and then to assess the potential for endo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 51 publications
0
10
0
Order By: Relevance
“…Xu et al (2022) reported that the TPS and CYP450 gene families might also contribute to alkaloid biosynthesis in D. nobile . Wang et al (2022) reported that two dendrobine-type sesquiterpenoid alkaloids (6-hydroxydendrobine and nobilonine) from the Dendrobium endophytic bacterium Pseudomonas protegens CHA0 were synthesized mainly through the MEP pathway . However, the mechanism through which Phyllosticta stimulates dendrobine accumulation is still unclear and requires further exploration.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Xu et al (2022) reported that the TPS and CYP450 gene families might also contribute to alkaloid biosynthesis in D. nobile . Wang et al (2022) reported that two dendrobine-type sesquiterpenoid alkaloids (6-hydroxydendrobine and nobilonine) from the Dendrobium endophytic bacterium Pseudomonas protegens CHA0 were synthesized mainly through the MEP pathway . However, the mechanism through which Phyllosticta stimulates dendrobine accumulation is still unclear and requires further exploration.…”
Section: Discussionmentioning
confidence: 99%
“…The population dynamics and distribution of endophytic fungi are primarily dependent on the availability of host species-specific habitats, organs, nutrients, and climatic factors . Research on D. nobile suggests that endophytic bacterial community structure is dependent on stem length . However, exogenous fungi, growing or originating from outside an organism, are abundant in natural environments, particularly in polluted environments. , Exogenous fungi can improve the stress resistance of their host plants, including to pathogens, drought, and heavy metals .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…207 It is noteworthy that 6-hydroxydendrobine ( 97 ) and nobilonine ( 109 ) were identified from the endophyte ( Pseudomonas protegens CHA0, 99.24%), which was isolated from the Dendrobium stems and the entire-genome analysis resulted in the biosynthesis of FPP mainly via the MEP pathway. 208…”
Section: Biosyntheses Of Picrotoxane Sesquiterpenoidsmentioning
confidence: 99%
“…They have been isolated and cultured from the roots and above-ground parts of various plants, including algae, mosses, ferns, gymnosperms, and angiosperms. Evidence from microorganism's records in the fossil plant tissue indicated that the plant-endophytic fungal interactions have existed for approximately 400 million years, and during this time, endophytic fungi co-evolved unique biosynthetic pathways and metabolic mechanisms to synthesize complex secondary metabolites [13]. To date, only 5% of 1.5 million fungal species on Earth have been described in detail, and out of this percentage (69,000 fungal species), only 16% (11,500 species) have been cultured and studied.…”
Section: Introductionmentioning
confidence: 99%